Chromatin fragmentation associated with apoptotic changes in tobacco cells exposed to cold stress - Koukalová, B; Kovarík, A; Fajkus, J; Siroký, J (FEBS letters, 1997)
Programmed cell death (PCD) may be triggered by a variety of environmental stimuli. In this report we show that low temperature treatment of tobacco BY-2 cells results in specific chromatin changes. The early stage was characterised by chromatin condensation associated with specific endonucleolytic cleavage of the genome into fragments of 50-100 kbp in size. Later, after 2 weeks of the cold treatment, a ladder of nucleosomal units (178 bp) and their multiples occurred. Chromatin changes were accompanied by a general decrease in cell viability. However, the cell culture retained about 11% of living cells even after prolonged incubation in the cold suggesting the presence of a cold-resistant population of cells. The results support the view that PCD was activated by the cold stress. We suggest that cold-stressed tobacco BY-2 culture might be a useful system for investigation of PCD in plant cells.
Keywords: kultivované buňky; nízká teplota; Cold Temperature; Cells, Cultured; DNA, Ribosomal; ribozomální DNA; Plants, Toxic; apoptóza; DNA rostlinná; tabák; DNA Fragmentation; Apoptosis; Cell Nucleus; Nucleosomes; fragmentace DNA; Chromatin; buněčné jádro; nukleozomy; Nicotiana; DNA, Plant; jedovaté rostliny; RNA ribozomální; chromatin; RNA, Ribosomal